Identifying Pathways for More Gender-Sensitive Communication Channels in Climate Services - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The brief is a result of synthesis of CCAFS CIS programming to date for gender results and implications. The brief will provide a basis for planning future projects that are gender-responsive, and is one step towards developing a gender-transformative framework for CIS.